Mitochondria during sea urchin oogenesis. Issue 2 (9th March 2017) - Agnello, Maria; Roccheri, Maria Carmela; Morici, Giovanni; Rinaldi, Anna Maria
Summary: Sea urchin represents an ideal model for studies on fertilization and early development, but the achievement of egg competence and mitochondrial behaviour during oogenesis remain to be enlightened. Oocytes of echinoid, such as sea urchin, unlike other echinoderms and other systems, complete meiotic maturation before fertilization. Mitochondria, the powerhouse of eukaryotic cells, contain a multi-copy of the maternally inherited genome, and are involved directly at several levels in the reproductive processes, as their functional status influences the quality of oocytes and contributes to fertilization and embryogenesis. In the present paper, we report our latest data on mitochondrial distribution, content and activity during Paracentrotus lividus oogenesis. The analyses were carried out using confocal microscopy, in vivo incubating oocytes at different maturation stages with specific probes for mitochondria and mtDNA, and by immunodetection of Hsp56, a well known mitochondrial marker. Results show a parallel rise of mitochondrial mass and activity, and, especially in the larger oocytes, close to germinal vesicle (GV) breakdown, a considerable increase in organelle activity around the GV, undoubtedly for an energetic aim. In the mature eggs, mitochondrial activity decreases, in agreement with their basal metabolism. Further and significant information was achieved by studying the mitochondrial chaperonin Hsp56 and mtDNA. Results show a high increase of both Hsp56 and mtDNA. Taken together these results demonstrate that during oogenesis a parallel rise of different mitochondrial parameters, such as mass, activity, Hsp56 and mtDNA occurs, highlighting important tools in the establishment of developmental competence.